Personnel management in the conditions of digitalization - Smolinets, I.; Levkiv, H. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
Human resource management in the digital industry has become inextricably linked to digitalization. With the development of information technology a new digital advances lead to the transformation of business organizations and leads to the emergence of new innovative methods, unique systems and processes. The concept of digital transformation is closely linked to digitalization and digital innovation. All these concepts are based on digital technologies, and the introduction of innovative methods and digitalization will change the main activities. To gain a competitive advantage, companies need to introduce new methods to manage these complex transformations. And more and more attention is paid to finding talents that are best suited for a particular company, and controlling the situation in a rapidly changing environment. The author draws attention to the transformation of the most important management subsystem - the impact of the digital economy on the personnel management system. In this context, it is important to bridge the existing gap in the literature, to understand how the introduction of innovative approaches to personnel management can support both complex processes, finding the parameters needed to assess and predict effectiveness. The purpose of this study is to substantiate the need for innovative methods of staff development in the context of digitalization. The article considers the main theoretical provisions of digitalized personnel management, the main methods and innovative tools that can help managers at different levels to work effectively with different scenarios of staff work. Based on the research, we came to the conclusion that it is necessary to implement innovative programs, development programs and personnel management programs using digital capabilities.